A Comparative Study of Cardiovascular Response and Analgesic Effects of Bupivacaine and Butorphanol - Keshava Murthy MR; Vikas KN (Academia Anesthesiologica International, 2019)
Background: Several methods have been used to relieve post-operative pain, among which epidural administration of local anaesthetic and opioids gained popularity. While proving analgesia through epidural route, cardiovascular response of epidural administered 0.25% bupivacaine with 2mg butorphanol. Subjects and Methods:50 patients between 40-50 years of age undergoing hysterectomy randomly allotted to 2 groups of 25 patients in each group. Group I received 10ml of 0.25% Bupivacaine and Group II received 2 mg Butorphanol diluted in 18ml of normal saline via epidural placed catheter before giving General Anaesthesia for performing hysterectomy. The general anaesthesia technique was the same in both groups of patients. Cardiovascular responses like heart rate, systolic blood pressure, diastolic blood pressure and mean arterial pressure were monitored post-operatively for 10 hrs. Onset of analgesia, duration of analgesia and side effects like nausea, vomiting and sedation were also noted. Results: Heart rate were similar between 2 groups before and after injection of drugs into the epidural space (P>0.05). There was decrease in the mean systolic blood pressure (P<0.05), mean diastolic blood pressure (P<0.001) and mean arterial pressure (P<0.001) in group I. Onset of analgesia was faster with butorphanol(11.76 minutes) when compared to Bupivacaine(14.38 minutes) and duration of analgesia was longer with butorphanol(7.48 minutes) when compared with Bupivacaine(6.67 minutes).Side effects like nausea, vomiting were more with Bupivacaine (20%) and sedation was the main side effect with butorphanol (40%). Conclusion: Our study concludes that epidural administration 10ml of 0.25% Bupivacaine causes significant hypotension when compared to 2mg Butorphanol with 8ml of normal saline given epidural. Butorphanol in epidural space has quicker and longer analgesic action than 0.25% bupivacaine.